Anthropological Insights into Mogigi: The Intersection of Kaili Custom and Islamic Law - Nur Rahmi, Irma (DIKTUM: Jurnal Syariah dan Hukum, 2024)
This article contains an anthropological review of Islamic law on traditional marriages in the Kaili community which carry out marriage rituals by requiring the practice of mogigi. Mogigi is the process of shaving the fine hairs around the eyebrows without changing the original structure of the eyebrows which is done on both bride and groom. Based on this custom, this study aims to describe the process of implementing the mogigi tradition in traditional marriages of the Kaili community and to explain the anthropological review of Islamic law on this tradition. This research is a qualitative research (field research) with an anthropological approach to Islamic law which accumulates the principles of Fiqhiyyah, Urf and the theory of Symbolic Interpretivism by Clifford Geertz. The data sources used by researchers consist of primary data (interviews) and secondary data in the form of books, journals and manuscripts. The results of this study concluded that the mogigi tradition is a traditional symbol of the Kaili tribe which has a symbolic meaning as a manifestation of the willingness, obedience, and belief of the bride and groom to leave all their past deeds, and be ready to face the future with fortitude. After conducting in-depth research on all aspects of adat in the mogigi tradition, it can be seen that the mogigi tradition does not conflict with Islamic law, because a taghyir (Adaptive-reconstructive) process has taken place between the local culture of the Kaili indigenous people and Islamic law resulting in the mogigi tradition. which contain cultural values ​​and Islamic values. This research has implications for the existence of the mogigi tradition in the traditional wedding procession of the Kaili tribe which has experienced a mixture of religious and cultural values.